AB0065 Galectin-3 Is A Major Determinant of Femoral Neck Bone Mineral Density in A Partial Regression Model: A Preliminary Study. (15th July 2016) - Ko, C.; Su, Y.-J.
Abstract : Background: Low bone mass is an essential extra-articular feature of rheumatoid arthritis (RA). Patients with RA might present an increased risk of low bone mass as a result of systemic inflammation by alteration of the RANK/RANKL/osteoprotegerin and Wnt/ catenin pathways. In RA, serum galectin-3 correlated with C-reactive protein levels and was considered as biomarker of inflammation. However, recent studies showed abundant galectin-3 observed in the area of severe bone destruction may act as a negative regulator for the upregulated osteoclastogenesis. The role of Galectin-3 is unclear in the regulation of bone resorption in RA. Objectives: The objectives of our study were to evaluate bone mineral density (BMD) and the levels of Galactin-3 and Dkk-1 in RA patients and to study the relation between these parameters. Methods: Patients with active RA were checked with galactin-3, Dkk-1 and followed up with BMD assessment and inflammatory evaluation by ultrasonography (US). Serum galectin-3, Dkk-1 concentrations were assayed with ELISA assay. BMD was measured at hip neck by a Dual-energy X-ray absorptiometry (DXA) (Explorer; Hologic Inc., USA). Grey scale and Power doppler US were graded using a 4-grade semiquantitative scoring system, on a scale of 0–3 at wrist. Each wrist was scanned from lateral to medial aspects in longitudinal planes Radius-Lunate-capitate (volar and dorsal), dorsal Radius-scaphoid-trapezoid, and dorsal Ulna-triquetral. Demographic and clinical data, DAS-28, and erythrocyte sedimentation rate (ESR) were recorded for each patient. Correlations between variables and multilinear regression analysis were performed to check serum galectin-3 expression levels and BMD parameters. Results: (1) Six RA patients 50% were female, age was 57.3±4.4 years, disease duration was 6.9±3.8 years and disease activity DAS 28 was 6.33±0.31. (2) The galectin-3, Sonography inflammatory score and serum iPTH levels showed a significant negative association with BMD at the hip.(Table.1 ) (3) The multilinear regression analysis showed iPTH, Galactin3 and US score were found to explain 99% of the variance in BMD in hip neck.(4) However, the galectin-3 in multilinear regression analysis showed a positive association with BMD at the hip. (correlation coefficient=0.126, p value=0.014) (Table.2 ) Conclusions: Galectin-3 is a major determinant of femoral neck BMD in this partial regression model, after controlling iPTH and sonography inflammatory score, in our preliminary study. References: Diarra, Danielle, et al. Nature medicine 13.2 (2007): 156–163. Ohshima, Shiro, et al. Arthritis & Rheumatism 48.10 (2003): 2788–2795. Li, Yin-Ji, et al. Laboratory Investigation 89.1 (2009): 26–37. Disclosure of Interest: None declared